Treatment and Controversies in Paraesophageal Hernia Repair - Lebenthal, Abraham; Waterford, Stephen D.; Fisichella, P. Marco (Frontiers in Surgery, 2015)
Background: Historically all paraesophageal hernias were repaired surgically, today intervention is reserved for symptomatic paraesophageal hernias. In this review, we describe the indications for repair and explore the controversies in paraesophageal hernia repair, which include a comparison of open to laparoscopic paraesophageal hernia repair, the necessity of complete sac excision, the routine performance of fundoplication, and the use of mesh for hernia repair. Methods: We searched Pubmed for papers published between 1980 and 2015 using the following keywords: hiatal hernias, paraesophageal hernias, regurgitation, dysphagia, gastroesophageal reflux disease, aspiration, GERD, endoscopy, manometry, pH monitoring, proton pump inhibitors, anemia, iron deficiency anemia, Nissen fundoplication, sac excision, mesh, mesh repair. Results: Indications for paraesophageal hernia repair have changed, and currently symptomatic paraesophageal hernias are recommended for repair. In addition, it is important not to overlook iron-deficiency anemia and pulmonary complaints, which tend to improve with repair. Current practice favors a laparoscopic approach, complete sac excision, primary crural repair with or without use of mesh, and a routine fundoplication.